A Review Of Victimology Of Victims Of Online Fraud In E-Commerce Transactions In Karawang Regency In Connection With The Lifestyle Exposure Theory - Marga Reta Donia Kartika; Zarisnov Arafat; Muhamad Abas (Journal of Law, Politic and Humanities, 2026)
Unilateral This research is motivated by the high number of cybercrimes in the form of fraud in e-commerce in Karawang Regency, with the increasing digital lifestyle of the community. The main objective of this study is to explore this phenomenon using a victimology perspective, where the Lifestyle Exposure theory of Hindelang and his colleagues and the concept of functional responsibility of Stephen Schafer are the foundation. The methodology applied in this study is empirical juridical, with primary data obtained through in-depth interviews with the Tipidter Unit of the Karawang Police and individuals who have become victims of online fraud. The findings of the study indicate that the key factors causing victimization in Karawang are caused by less vigilant consumer behavior, including transactions outside official platforms (85%) and being influenced by unreasonable prices (78%), which theoretically indicates exposure to risks due to digital lifestyles. The Karawang Police's countermeasures utilize a preventative approach, providing digital literacy education to strengthen social resilience, and a repressive approach through law enforcement based on digital forensics and inter-agency collaboration (Kominfo, BSSN, and OJK) to create a deterrent effect on perpetrators. This study concludes that preventing online fraud requires collaboration between legal enforcement and increased awareness among victims to break the cycle of opportunity for crime.